CONCEPTUAL STRUCTURE OF THE SYSTEM OF DOMESTIC TRADE IN CONSUMER GOODS AND SERVICES (Development Service Industry Management, 2023)
The article provides a scientific substantiation of the conceptual structure of the system of domestic trade in consumer goods and services, highlighting the purpose of functioning, the branch-sectoral subsystem and the subsystem of regulation of the development of domestic trade. The systemic role and nature of the functioning of domestic trade in consumer goods and services has both primary and resulting features. Actually, the positive effects and results for the country and its territories are consequential, while the formation of a full-fledged internal trade system in the studied sector of the economy is primary. This is the relevance of the theoretical and methodological formulation of the problem of identification of the composition and structure of the elements of such a system. It has been established that the purpose of the functioning of internal trade is the effective and full realization of the functions of trade in the system of the national economy, in particular with regard to ensuring the processes of exchanging goods and services for money / another equivalent of expressing their value or price), satisfying the economic interests of sellers in the sale of products (goods, services ) and the needs of buyers and end consumers in goods (services), the growth of domestic production and increasing the capacity of the domestic market, the implementation of social tasks. The system of internal trade in goods and services is divided into two subsystems - (1) conditionally «structural-static» (industry-sectoral subsystem consisting of elements of functional, organizational, social and territorial blocks) and (2) «functional-dynamic» (regulation of development with elements of institutional, environmental and resource conditions of management in the field of trade, strategic and operational tools of management, expected results and criteria for checking their achievement). It is with a systematic approach to the functional-structural decomposition of domestic trade in consumer goods and services that a much better understanding of the principles of functioning and approaches to the regulation of trade in the consumer market emerges.
Keywords: internal trade; consumer goods and services; public administration; internal market